Maize Zmcyp710a8 Mutant as a Tool to Decipher the Function of Stigmasterol in Plant Metabolism - Aboobucker, Siddique I.; Showman, Lucas J.; Lübberstedt, Thomas; Suza, Walter P. (Frontiers in Plant Science, 2021)
Sterols are integral components of membrane lipid bilayers in eukaryotic organisms and serve as precursors to steroid hormones in vertebrates and brassinosteroids (BR) in plants. In vertebrates, cholesterol is the terminal sterol serving both indirect and direct roles in cell signaling. Plants synthesize a mixture of sterols including cholesterol, sitosterol, campesterol, and stigmasterol but the signaling role for the free forms of individual plant sterols is unclear. Since stigmasterol is the terminal sterol in the sitosterol branch and produced from a single enzymatic step, modifying stigmasterol concentration may shed light on its role in plant metabolism. Although Arabidopsis has been the model of choice to study sterol function, the functional redundancy of AtCYP710A genes and the presence of brassicasterol may hinder our ability to test the biological function of stigmasterol. We report here the identification and characterization of ZmCYP710A8, the sole maize C-22 sterol desaturase involved in stigmasterol biosynthesis and the identification of a stigmasterol-free Zmcyp710a8-1 mutant. ZmCYP710A8 mRNA expression pattern correlated with transcripts for several sterol biosynthesis genes and loss of stigmasterol impacted sterol composition. Exogenous stigmasterol also had a stimulatory effect on mRNA for ZmHMGR and ZmSMT2. This demonstrates the potential of Zmcyp710a8 in understanding the role of stigmasterol in modulating sterol biosynthesis and global cellular metabolism. Several amino acids accumulate in the Zmcyp7108 mutant, offering opportunity for genetic enhancement of nutritional quality of maize. Several other cellular metabolites in roots and shoots of maize and Arabidopsis were also impacted by genetic modification of stigmasterol content. Yet lack of obvious developmental defects in Zmcyp710a8 suggest that stigmasterol might not be essential for plant growth under normal conditions. Nonetheless, the Zmcyp710a8 mutant reported here is of great utility to advance our understanding of the additional roles of stigmasterol in plant metabolism. A number of biological and agronomic questions can be interrogated using this tool such as gene expression studies, spatio-temporal localization of sterols, cellular metabolism, pathway regulation, physiological studies, and crop improvement.